Place attachment in historical commercial setting a case study of Davao City Chinatown - Mahinay, Marvin C. (2023)
For decades, different nations around the world have been following the trend of globalization. Globalization increases the interconnectedness and interdependence of peoples and countries. This connection allowed the rampant exchange of goods, ideas, technology, etc. around every corner of the world. This led to the rapid emergence of infrastructure, shops, and buildings in various community public spaces. The study?s main concern is that because of the effects of globalization and the recent COVID-19 pandemic a lot of people may get the feeling of being disconnected to the place which could result to placelessness. In order to revive the place and restore its vibrancy, the researcher aims to discover how the local community of Chinatown can obtain a renewed sense of place attachment among the local community of Chinatown. The study utilized a descriptive qualitative and quantitative research design, and a survey questionnaire and interview were conducted on both static and mobile users inside the Chinatown for the primary data collection.To determine other factors such as vibrancy, and traffic an on-site observation was also used. The study revealed that the major elements that were highly correlated with the emotional and functional attachment of the people in Davao City Chinatown: Accessibility, Vitality, Comfortability, Cultural Designs or Chinese-inspired Designs, and Shopping Mall (NCCC Mall). These results were fundamental in making architectural issues and the overall design development of the proposed project.